Alterations in fecal bacteriome virome interplay and microbiota-derived dysfunction in patients with schizophrenia - Shiwan Tao; Yulu Wu; Liling Xiao; Yunqi Huang; Han Wang; Yiguo Tang; Siyi Liu; Yunjia Liu; Qianshu Ma; Yubing Yin; Minhan Dai; Min Xie; et al. (Translational Psychiatry)
Abstract Rising studies have consistently reported gut bacteriome alterations in schizophrenia (SCZ). However, little is known about the role of the gut virome on shaping the gut bacteriome in SCZ. Here in, we sequenced the fecal virome, bacteriome, and host peripheral metabolome in 49 SCZ patients and 49 health controls (HCs). We compared the gut bacterial community composition and specific abundant bacteria in SCZ patients and HCs. Specific gut viruses and host peripheral metabolites co-occurring with differential bacteria were identified using Multiple Co-inertia Analysis (MCIA). Additionally, we construct a latent serial mediation model (SMM) to investigate the effect of the gut virome on SCZ through the bacteriome and host metabolic profile. SCZ patients exhibited a decreased gut bacterial β-diversity compared to HCs, with seven differentially abundant bacteria, including Coprobacillaceae, Enterococcaceae etc. Gut viruses including Suoliviridae and Rountreeviridae, co-occur with these SCZ-related bacteria. We found that the viral-bacterial transkingdom correlations observed in HCs were dramatically lost in SCZ. The altered correlations profile observed in SCZ may impact microbiota-derived peripheral metabolites enriched in the bile acids pathway, eicosanoids pathway, and others, contributing to host immune dysfunction and inflammation. The SMM model suggested potential causal chains between gut viruses and SCZ, indicating that the effect of gut virome on SCZ is significantly mediated by bacteriome and metabolites. In conclusion, these findings provide a comprehensive perspective on the role of gut microbiota in the pathogenesis of SCZ. They reveal that patients with schizophrenia harbor an abnormal virome-bacteriome ecology, shedding light on the potential development of microbial therapeutics.